Effects of 0.4% ripasudil hydrochloride hydrate on morphological changes in rabbit eyes - Limratchatamorn, Bundit (Int J Ophthalmol, 2019)
We evaluated the cellular structure changes after continuous use of ripasudil hydrochloride hydrate in rabbit eyes which might affect its own efficacy and adverse effects. Two pigmented Dutch rabbits and 1 Japanese white rabbit were instilled with 0.4% ripasudil hydrochloride hydrate to the left eye twice daily. The right eye was observed as the control. Both eyes of all 3 rabbits were then enucleated for histopathologic examination by light and electron microscope at 1mo in 1 of the pigmented Dutch rabbits, 3mo in the other pigmented Dutch rabbit, and in the Japanese white rabbit after instillation. Microscopic observations showed increase intercellular space in trabecular meshwork, ciliary body, and iris stoma, increase pigmented granule number and size in iris epithelial cells, and decrease actin filament in iris muscle fiber cells. Consequently, ripasudil hydrochloride hydrate decreases the intraocular pressure by improving the conventional outflow and may also facilitate the unconventional outflow via intercellular space widening without serious side effects.